EXPERIMENTAL STUDY ON THE PLANE STRAIN DYNAMIC FRACTURE TOUGHNESS OF 20CRMNTI BASED ON IMPROVED HPB PLATFORM - SONG Kun; ZHANG XiaoDi; DING Jun; HUANG Xia; HE XiaoJin; WANG JiaBin; WANG LuSheng (Jixie qiangdu)
To obtain the dynamic fracture toughness of 20 Cr Mn Ti,an impact loading test was conducted on three-point bending specimens with the improved Hopkinson pressure bar.Dynamic stress intensity factor was determined by the spring mass model.The onset time of crack initiation is experimentally detected using the strain gauge method.Dynamic fracture toughness of20 Cr Mn Ti with type I crack was obtained through the above experimental procedure.The geometrical dispersion distortion caused by lateral inertia effect is effectively inhibited by the wave shaping technique,to ensure the consistency of stress wave signal in measuring point and loading point is guaranteed.At the same time,the high-speed camera system was used to collect the image and the change of the surface strain field during the loading process was analyzed with GOM Correlate.The results show that samples before crack initiation has reached the dynamic strain balance,ensure the validity of the experiment.